PARENTS' INTEREST IN AUD EDUCATION 2-4 YEARS - Erna Budiarti; Tri Rahayu Budiarti; Noor Padilah; Wirastri Setyorini; Masita Nunlehu (Jurnal Scientia, 2022)
Parents have the responsibility to provide the best education for their children. One of the obligations of parents is to provide and choose schools according to the needs and readiness of learning children. However, there are many obstacles, parents' unconsciousness, and abilities that become barriers for children to get an education at school. Based on the background of this research, there is low interest from parents to send their children to PAUD institutions in Binuang District, Tapin Regency, South Kalimantan. The research aims to find out the factors that influence the interest of parents who do not want to include their children in playgroups (KB). The research subjects were parents who did not send their children to school in the Play Group which was the sample selection criteria, Binuang District, Tapim Regency. The method used in this study is a qualitative method supported by quantitative data. Quantitative data were obtained using data collection techniques using questionnaires at 7 PAUD institutions that have Playgroup services with 100 respondents. The average respondent who has an interest in sending their child to school is influenced by the needs, personal goals/motives of the parents, and the needs of the child. However, economic factors, and parents' educational background, are the highest percentage of interest in sending their children to school.